Analysis of the Level of Knowledge about Pedophilia in School Children - Reina Dhamanik; Nikmatul Khayati; Machmudah Machmudah (Universitas Muhammadiyah Semarang, 2026)
Sexual misconduct has existed since long ago, and every year millions of children are exposed to various forms of abuse. Pedophilia among children in Demak has become a phenomenon that must be handled properly between perpetrators and victims. Pedophilia among children: Incidents of child pedophilia will disrupt the balance of children's thought processes in the future regarding the concept of sexuality. Pedophilia and child sexual abuse require in-depth scientific knowledge to improve prevention strategies in society. The purpose of this study is to analyze the level of knowledge about pedophilia among school children in the Demak region of Indonesia. The research method used descriptive analysis with the CKAQ questionnaire, including children's knowledge related to pedophilia and sexual deviance, with a sample of 196 children with an average age of 10-11 years. The results of the study show that there are still students who lack understanding about pedophilia in the low to moderate range. The conclusion of the study shows that the level of knowledge among schoolchildren regarding pedophilia still needs to be improved through regular education on the importance of knowing and maintaining reproductive health and understanding the correct concept of sexuality.